KONSTRIBUSI PAJAK DAERAH TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN PAMEKASAN - R Agoes Kamaroellah (Institut Agama Islam Negeri Madura, 2015)
The purpose of this reserach was to know how much the contribution of the regional tax towards the original revenue of region on revenue (PAD) in regency of Pamekasan in 2011 to 2015. In accordance to the data contained in Revenue Department , Financial management and Regional Asset in Pamekasan Regency of Local tax from 2011 to 2015 more increasing so that the original revenue of region also increase. Thus local taxes contribute to local revenues. The results of the analysis in chapter discussion obtained the contribution magnitude of local tax to original revenue of region as follows: Contributions of local taxes to the original revenue of region in 2011 amounted to 15.7%, in 2012 by 17:13%, in 2013 by 1:33%, 2014 at 13:52% and the 2015 amounted to 13.78%. So that on average each year, reaching 12% local tax contributions toward the original revenue of region